2021
DOI: 10.3390/gels7030078
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Thermogelation and Rheology of Poly(2-Oxazoline)/Poly(2-Oxazine)s Based Thermosensitive Hydrogels for 3D Bioprinting

Abstract: As one kind of “smart” material, thermogelling polymers find applications in biofabrication, drug delivery and regenerative medicine. In this work, we report a thermosensitive poly(2-oxazoline)/poly(2-oxazine) based diblock copolymer comprising thermosensitive/moderately hydrophobic poly(2-N-propyl-2-oxazine) (pPrOzi) and thermosensitive/moderately hydrophilic poly(2-ethyl-2-oxazoline) (pEtOx). Hydrogels were only formed when block length exceeded certain length (≈100 repeat units). The tube inversion and rheo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 99 publications
(150 reference statements)
0
17
0
Order By: Relevance
“…Haider et al [ 207 ] reported recently a smart thermosensitive 3D network formed by a diblock copolymer of approximately 100 repeating units containing hydrophobic poly(2-N-propyl-2-oxazine) (pPrOzi) and hydrophilic poly(2-ethyl-2-oxazoline) (pEtOx), suitable for extrusion-based 3D printing ( Figure 11 ). The rheological investigations evidenced the gelation as a function of temperature and concentration, the viscoelastic and shear-thinning behavior, as well as the ability of rapid structure recovery, the hydrogel being suitable for tissue engineering applications (cell viability ≈ 97%).…”
Section: Rheology As a Prerequisite For Bioink Formulation And Optimi...mentioning
confidence: 99%
“…Haider et al [ 207 ] reported recently a smart thermosensitive 3D network formed by a diblock copolymer of approximately 100 repeating units containing hydrophobic poly(2-N-propyl-2-oxazine) (pPrOzi) and hydrophilic poly(2-ethyl-2-oxazoline) (pEtOx), suitable for extrusion-based 3D printing ( Figure 11 ). The rheological investigations evidenced the gelation as a function of temperature and concentration, the viscoelastic and shear-thinning behavior, as well as the ability of rapid structure recovery, the hydrogel being suitable for tissue engineering applications (cell viability ≈ 97%).…”
Section: Rheology As a Prerequisite For Bioink Formulation And Optimi...mentioning
confidence: 99%
“…Furthermore, hADSC stem cells were efficiently encapsulated, and the hydrogel showed cytocompatibility in post-printing cell experiments. This hydrogel can be an alternative in combination with other bioinks to improve printability or be used as a drug delivery platform [ 88 ].…”
Section: Advances and Applications Of Block Copolymers In 3d/4d Print...mentioning
confidence: 99%
“…39 Very recently, Haider et al introduced an alternative in with the PMeOx block was exchanged with an poly(2-ethyl-2-oxazoline). 40 However, the lacking long-term stability of the printed constructs remains a major drawback -upon addition of excess cell culture media necessary for longer-term cell culture, these constructs will simply dissolve. Hahn et al reported on cytocompatible ABA-type triblock copolymers comprising the same PMeOx as the hydrophilic blocks (A) and poly(2-phenyl-2-oxazine), poly(2-phenethyl-2-oxazoline) or poly(2-benzhydryl-2-oxazine), respectively, as the hydrophobic block (B).…”
Section: Introductionmentioning
confidence: 99%